2009
DOI: 10.1136/ard.2008.104786
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-1 is essential for systemic inflammatory bone loss

Abstract: These data indicate that IL1 is essential for TNF-mediated bone loss. Despite TNF-mediated inflammatory arthritis, systemic bone is fully protected by the absence of IL1, which suggests that IL1 is an essential mediator of inflammatory osteopenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
78
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(88 citation statements)
references
References 26 publications
7
78
0
3
Order By: Relevance
“…The notion of IL-1-mediated bone loss also is supported by a study where inhibition of IL-1 with soluble IL-1R was shown to significantly reduce inflammation, loss of connective tissue and bone resorption in the periodontium of Macaca fascicularis primates infected with pathogens (23). A different study showed that IL1 -/-hTNFtg mice were completely protected from systemic bone loss mediated through the overexpression of TNF-α (24). A possible pathogenetic role for IL-1β in bone loss is further supported by the fact that IL-1β enables peripheral blood mononuclear cells to differentiate into osteoclasts in the presence of osteoblastic SaOS-2 cells without further stimulation (25).…”
Section: Il-1β Inhibits Human Osteoblast Migrationmentioning
confidence: 57%
“…The notion of IL-1-mediated bone loss also is supported by a study where inhibition of IL-1 with soluble IL-1R was shown to significantly reduce inflammation, loss of connective tissue and bone resorption in the periodontium of Macaca fascicularis primates infected with pathogens (23). A different study showed that IL1 -/-hTNFtg mice were completely protected from systemic bone loss mediated through the overexpression of TNF-α (24). A possible pathogenetic role for IL-1β in bone loss is further supported by the fact that IL-1β enables peripheral blood mononuclear cells to differentiate into osteoclasts in the presence of osteoblastic SaOS-2 cells without further stimulation (25).…”
Section: Il-1β Inhibits Human Osteoblast Migrationmentioning
confidence: 57%
“…Moreover, IL-17, like IL-1 can elicit cartilage degradation alone or in combination with other cytokines [36,37]. Herein, we show that in the context of TNF-a-driven inflammation, inhibition of IL-17 shared stunning similarities with IL-1 inhibition, as single inhibition of neither IL-1 nor Il-17 effectively inhibits TNF-a-mediated synovial inflammation whereas both strategies are highly effective to protect from local and systemic bone loss as well as cartilage breakdown [6,38]. This observation indicates that inflammatory pathways downstream of TNF-a, such as IL-1 and IL-17, act simultaneously for building up synovial inflammation.…”
Section: Discussionmentioning
confidence: 89%
“…Disease starts at the age of 6 weeks and is accompanied by local and systemic bone loss reflecting inflammatory bone disease of human rheumatoid arthritis. hTNFtg were also intercrossed with IL-1 À/À mice (genetic background C57BL/6 [38,43]). F2 generations were identified by PCR genotyping of the tail using the following primers: hTNF transgene: 5 0 -TACCCC-CTCCTTCAGACACC-3 0 and 5 0 -GCCCTTCATAATATCCCCCA-3 0 ; IL-1a/b primers were as follows: IL-1aF, 5 0 -CTTGGCCATACTG-CAAAGGTCATG-3 0 , IL-1aR, 5 0 -CAGGTCATTTAACCAAGTGGTGC-TG-3 0 ; IL-1a/b KO, 5 0 -GAGGTGCTGTTTCTGGTCTTCACC-3 0 ; IL-1bF, 5 0 -GCGAATGTGTCACTATCTGCCACC-3 0 ; IL-1bR, 5 0 -CCATGCCACAGTCCCTCCAC-3 0 ; In the present study, a total of 45 mice were included and only littermates were used.…”
Section: Animals and Treatmentmentioning
confidence: 99%
“…In line with the known effect on growth plate and fracture callus cartilage (16), in our model IL-1β induced (i) enhanced MMP-13-mediated endogenous ECM preprocessing; (ii) enhanced host osteoclastmediated ECM remodeling by increased M-CSF levels and RANKL/OPG ratios; (iii) faster vascularization, despite a minimal reduction in VEGF content (15); and (iv) larger regions of BM, possibly because of an increased synthesis of SDF1, IL-8, M-CSF, and MCP-1. Instead, IL-1β did not induce a reduction of bone mass by increased bone resorption (24), because its administration was temporally confined to the phase preceding bone matrix deposition. Further studies are required to validate the functionality of the engineered bone organ in the context of an immunocompetent model at an orthotopic site, where loading and inflammation would further regulate bone development and homeostasis.…”
Section: Discussionmentioning
confidence: 99%